(untitled) (Annals of Medical Research, 2021)
Aim: To investigate whether pretreatment peripheral neutrophil/lymphocyte ratio (NLR) and platelet/lymphocyte ratio (PLR) can be used as a prognostic indicator for predicting treatment response and survival outcomes in patients with cervical cancer.Materials and Methods: Records of 141 patients with histologic confirmation of squamous cell carcinoma of the uterine cervix who were treated with radical radiotherapy or chemoradiotherapy in our clinic from 2010 to 2016 were retrospectively reviewed in this study. The relationship between pretreatment NLR/PLR with clinicopathological characteristics and therapeutic response and survival was analyzed. The cut-off values of NLR and PLR that predicted treatment response were determined using a receiver operating characteristic analysis.Results: In the clinicopathological analysis, while pretreatment elevated NLR was associated with the tumor size and grade, elevated PLR was related to an advanced stage, tumor size and grade. Low NLR (2.64) and PLR (164) predicted treatment response significantly. However, there was no relationship between NLR/PLR and survival outcomes. The five-year overall survival (OS) and progression-free survival (PFS) rates for the whole study group were 67% and 74%, respectively. In multivariate analysis, the presence of the lymph node involvement and incomplete response to treatment was independent prognostic factors affecting both OS (p = 0.013, p 0.001) and PFS (p = 0.004, p 0.001).Conclusion: Pretreatment NLR/PLR has predicted the treatment response significantly. The optimal cut-off values confirmed by further large-scale studies may be used in the future as a predictive marker for therapeutic response in cervical cancer.